2018
DOI: 10.1021/acs.jpcc.8b06836
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced S2 Fluorescence from a Free-Base Tetraphenylporphyrin Surface-Mounted Metal Organic Framework

Abstract: The ultrafast transient dynamics of a free-base tetraphenylporphyrin (H 2 TPP) surface-mounted metal organic framework (SURMOF) is spectroscopically characterized and compared with that of H 2 TPP in ethanol solution. A dramatic increase of the quantum yield of the Soret band fluorescence (S 2 → S 0 ) is observed in the H 2 TPP−SURMOF, which is accompanied by an increase of the S 2 fluorescence lifetime and a broadening of the fluorescence spectra. In contrast, the Q band (S 1 ) fluorescence is strongly quench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…The S 2 fluorescence lifetime for J‐type aggregated porphyrin is found to be varied from 130 fs to 1 ps . Sun and coworker have reported the fluorescence lifetime of S 2 state is 1.1–13 ps . Again, it is reported that the lifetime of S 2 ‐fluorescence varies from 1.4 ps to 3.4 ps with varying solvents .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The S 2 fluorescence lifetime for J‐type aggregated porphyrin is found to be varied from 130 fs to 1 ps . Sun and coworker have reported the fluorescence lifetime of S 2 state is 1.1–13 ps . Again, it is reported that the lifetime of S 2 ‐fluorescence varies from 1.4 ps to 3.4 ps with varying solvents .…”
Section: Resultsmentioning
confidence: 94%
“…[34,36,38,52] Sun and coworker have reported the fluorescence lifetime of S 2 state is 1.1-13 ps. [53] Again, it is reported that the lifetime of S 2 -fluorescence varies from 1.4 ps to 3.4 ps with varying solvents. [50,[54][55][56] With the disappearance of this stimulated emission, a rise time is observed which is same as the S 2 fluorescence lifetime.…”
Section: Femtosecond Transient Absorption Spectroscopymentioning
confidence: 98%
“…The femtosecond transient absorption spectra were obtained using a lab-made femtosecond pump–probe setup with 50 fs time resolution (see the details in the Supporting Information). The adsorption and desorption isotherms were obtained using an Autosorb iQ gas sorption analyzer (Quantachrome, USA) using N 2 at 77 K. The sample was outgassed at 150 °C for 5 h before the measurement. The specific surface areas were obtained using the Brunauer–Emmett–Teller method.…”
Section: Methodsmentioning
confidence: 99%
“…The potential energy functions of the states |e1 and |e2 cross at Q=1.8 (see Figure 1). The chromophore parameters are taken from a recent model describing the photophysics of the B and Qy states of free-base tetraphenylporphyrin [30]. Obviously, SM signals depend on specific values of the model parameters.…”
Section: Theoretical Frameworkmentioning
confidence: 99%